Association between skin sympathetic nerve activity and electrocardiogram alterations after subarachnoid hemorrhage - Yoichiro Nakagawa; Takashi Kusayama; Sho Tamai; Yuta Nagamori; Kazutaka Takeuchi; Shuhei Iwaisako; Taishi Tsutsui; Tomoya Kamide; Kouichi Misaki; Soichiro Usui; Kenji Sakata; Mitsutoshi Nakada; et al. (Physiological Reports)
Abstract While autonomic dysregulation and repolarization abnormalities are observed in subarachnoid hemorrhage (SAH), their relationship remains unclear. We aimed to measure skin sympathetic nerve activity (SKNA), a novel method to estimate stellate ganglion nerve activity, and investigate its association with electrocardiogram (ECG) alterations after SAH. We recorded a total of 179 SKNA data from SAH patients at three distinct phases and compared them with 20 data from controls. Compared with control data, in the acute phase data (days 1–3 of SAH), T peak‐to‐end (Tp‐e) interval was significantly prolonged (81 [interquartile range IQR: 71–93] vs. 58 [IQR: 54–64] ms, p < 0.001), non‐burst amplitude of SKNA was significantly increased (2.4 [IQR: 1.3–4.1] vs. 0.7 [IQR: 0.5–1.7] μV, p < 0.001), and the ratio of low frequency to high frequency (HF) was significantly decreased (0.8 [IQR: 0.5–1.1] vs. 1.1 [IQR: 0.7–1.3], p = 0.028). Linear mixed model revealed a relationship between Tp‐e interval and SKNA. Although these abnormalities gradually normalized, delayed cerebral ischemia episodes were associated with increased HF oscillation. Transient sympathetic dysregulation contributes to repolarization impairment after SAH. SKNA may have the potential to monitor adverse outcomes.